LEARNING DIALOGUE AS A MEANS OF ACTIVATION OF STUDENTS' COGNITIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2009)
The article deals with the essence of a dialogue training, developing of thinking and brisking up the pupils' training-cognitive activity.
Keywords: dialogue training; collective field of consciousness; construct subjective image of the object of cognition; thinking